An updated checklist of the Mexican Coccinellidae (Coleoptera) - Nestor-Arriola, Jorge Ismael; Toledo-Hernández, Víctor Hugo; Corona-López, Angélica María; Flores-Palacios, Alejandro (Zootaxa, 2026)
Through an extensive literature review and collections research an updated checklist of the Coccinellidae of Mexico is presented, the checklist includes a total of 353 species. New records of ladybird beetles for Mexico are also included: Neocalvia cayennensis (Gmelin), Mysia pullata (Say), and Eupalea clarki Almeida. The new taxonomic status for several species is proposed; new combinations as follows: Mulsantina luteipennis (Mulsant), Neda retrospiciens (Crotch), Cyrea levrati (Mulsant), Neoharmonia rugulosa (Sicard), and Zagreus bisbinotatus (Gorham); Brachiacantha brevihamata Nestor-Arriola & Toledo-Hernández as a new synonym of B. pygidialis Mulsant, Exochomus ixtlensis Casey as a new synonym of E. fasciatus Casey, and Mulsantina luteodorsa is a new synonym of M. luteipennis (Mulsant).